Mechanism and physiological significance of autoregulation of the Escherichia coli hfq gene - Morita, Teppei (RNA, 2019)
The RNA chaperone Hfq plays a critical role in sRNA-mediated gene regulation in enteric bacteria. The major role of Hfq is to stimulate base-pairing between sRNAs and target mRNAs by binding both RNAs through three RNA-binding surfaces. To understand the post-transcriptional network exerted by Hfq and its associated sRNAs, it is important to know how the cellular concentration of Hfq is regulated. While an early study showed that hfq translation is repressed by Hfq, the detailed mechanism and biological significance of the hfq autoregulation remain to be studied. Here, we show that the synthesis of Hfq is strictly autoregulated to maintain the cellular concentration of Hfq within a limited range even when the hfq mRNA is overexpressed from a plasmid-borne hfq gene. Mutational and biochemical studies demonstrate that Hfq represses its own translation primarily by binding to the hfq mRNA through the distal face. The growth of cells harboring the hfq plasmid is markedly inhibited due to an increased Hfq level when the distal face of Hfq is mutated or the 5′-UTR of hfq is mutated. A mutation in the rim suppresses the growth inhibition caused by the distal face mutation, suggesting that the interaction of Hfq with undefined RNAs through the rim is responsible for the growth inhibition by the increased Hfq level. In addition, the data suggest that the hfq autoregulation operates not only in cells harboring a multicopy hfq gene but also in the wild-type cells.